Dental caries and bacterial load in saliva and dental biofilm of type 1 diabetics on continuous subcutaneous insulin infusion - Coelho, Ana (2018)
Objectives: Since most of the studies evaluates diabetics on multiple daily injections therapy and continuous subcutaneous insulin infusion may help gain better metabolic control and prevent complications, the objective of this study was to evaluate the prevalence of dental caries, the unstimulated salivary flow rate and the total bacteria load, Streptococcus spp. levels and Lactobacillus spp. levels in saliva and supragingival dental biofilm of type 1 diabetics on insulin pump. Material and Methods: Sixty patients with type 1 diabetes on insulin pump and 60 nondiabetic individuals were included. The dental caries evaluation was performed using ICDAS and the oral hygiene was assessed according to Greene and Vermillion Simplified Oral Hygiene Index. Unstimulated saliva and supragingival dental biofilm were collected. Total bacteria, Streptococcus spp. and Lactobacillus spp. was quantified by qPCR. Results: Patients with type 1 diabetes had a higher prevalence of dental caries and filled and missing teeth when compared with the control group. These patients were associated with more risk factors for the development of dental caries, namely a lower unstimulated salivary flow rate and a higher bacterial load in saliva and dental biofilm. Conclusion: Some risk factors related to dental caries were associated with type 1 diabetics. An early diagnosis combined with the evaluation of the risk profile of the diabetic patient is imperative, allowing the dental caries to be analyzed through a perspective of prevention and the patient to be integrated into an individualized oral health program.